HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KECEPATAN LARI 60 METER SISWA KELAS VII SMPN 3 KECAMATAN SINGINGI - Jandri Palison; Drs. Ramadi., S.Pd., M.Kes AIFO '; Ardiah Juita., S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is running speed student distance of 60 meters not maximal yet, it is suspected because of leg muscle explosive power is less than optimal. This study aims to determine the corealtional of explosive power leg muscle with running speed 60 meters students class VII SMPN 3 Singingi District. This is a correlational study by comparing the measurement results of two different variables. A sample of 30 people using purposive sampling technique. The data in this study was obtained from the measurement results using the standing broad jump test for explosive power leg muscel and the running of 60 meters. Based on the research that has been done in students class VII SMPN 3 District of Singingi obtained r = 0.425, including the category enough. Tests of significance using the formula t test Significance. From the calculation results are known t = 2.485 while t table = 1.701. So t = = 2,485> t table = 1.701. Then it can be concluded as follows: There is a significant corealtion between the explosive power leg muscle with a running speed of 60 meter class VII SMPN 3 Singingi District.Keywords : Explosive Power, Leg Muscle, Running Speed 60 meters